2012
DOI: 10.1002/elps.201200026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the suitability of archival Bouin‐fixed paraffin‐embedded tissue specimens to proteomic investigation

Abstract: Bouin's solution has been used for over a century as a common fixative in several pathology laboratories worldwide. Therefore, a considerable number of Bouin-fixed paraffin-embedded (BFPE) tumor samples of various origin are available in hospital repositories as a powerful information mine for clinical investigations. To date, however, such archived tissues have not been subjected to a systematic study aimed to evaluate their potential use in proteomics. In this report, we investigated whether archival BFPE ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…For this purpose, in diagnostics, chemical fixatives are mainly used, and among them the most widely used is formalin, the aqueous solution of formaldehyde. However, Bouin’s fixative has been extensively used as an elective fixative for histological examination in some institutions worldwide [1]. Bouin’s fixative is a mixture of a saturated aqueous solution of picric acid, formalin, and acetic acid [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, in diagnostics, chemical fixatives are mainly used, and among them the most widely used is formalin, the aqueous solution of formaldehyde. However, Bouin’s fixative has been extensively used as an elective fixative for histological examination in some institutions worldwide [1]. Bouin’s fixative is a mixture of a saturated aqueous solution of picric acid, formalin, and acetic acid [2].…”
Section: Introductionmentioning
confidence: 99%
“…This fixation method has been used for specific purposes because it better preserves some morphological details, such as nuclear conformation [3]. In the past decades, several studies have already shown that Bouin’s-fixed samples are amenable for nucleic acid and protein analyses, but only to a certain point, as the fixative has resulted to be more detrimental compared to 10% buffered formalin mixture in the preservation of biomolecules [1,3,4]. Currently, no investigation has been carried out on the analysis performance with respect to miRNAs, despite the publication of two samples in a report [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to investigate whether Bouinfixed specimens are suitable for proteomic analysis using traditional MS-based techniques (e.g., GeLC-MS/MS) and have suggested that BFPE tissue archives can be fruitfully exploited for gathering data from particularly precious cases, although molecular biases and technical constraints exist. 14 While studies have presented the application of MALDI-MSI on BFPE tissues (e.g., human testis) with promising results, none have preceded to assess the technical reliability of this method through the direct parallel analysis of coupled FFPE cases. 15 Thus, starting from our previous results on FFPE renal biopsies in the context of different kidney diseases, 7,10,16−18 here we sought to investigate whether BFPE samples are equally suitable for spatial proteomics analysis with MALDI-MSI in order to further enrich the capabilities of this tool and, subsequently, unlock a wide retrospective series of rare renal diseases that can be exploited to increase our knowledge in this field.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In renal pathology, tissue specimens have routinely been treated with Bouin for years, and pathology archives are enriched in BFPE tissue, representing a goldmine to be untapped for molecular and diagnostic research techniques. Previous studies have attempted to investigate whether Bouin-fixed specimens are suitable for proteomic analysis using traditional MS-based techniques (e.g., GeLC-MS/MS) and have suggested that BFPE tissue archives can be fruitfully exploited for gathering data from particularly precious cases, although molecular biases and technical constraints exist . While studies have presented the application of MALDI-MSI on BFPE tissues (e.g., human testis) with promising results, none have preceded to assess the technical reliability of this method through the direct parallel analysis of coupled FFPE cases .…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of the latter technique is that it can be performed on formalin-fixed paraffin-embedded (FFPE) CRC patient tissue [31]. FFPE in combination with 2D-PAGE is still insufficient [32]. The use of frozen tumor tissue is applicable with 2D-PAGE.…”
Section: Proteomics Methodologymentioning
confidence: 99%